Muhammad Dandamayev - Dandamayev, Muhammad A. (Anabasis. Studia Classica et Orientalia, 2012)
This paper contains information on the military service of Central Asian soldiers in Babylonia during 539–331 B.C., when this country was a satrapy of the Achaemenid Persian empire. Among these soldiers were Chorasmians, Sakai and warriors from Arumāja. These soldiers were settled mainly in the region of Nippur allotting for their service parcels of land which were called “fiefs of the bow” for which they had to perform military service.